Using a Stakeholder Analysis to Implement the Belgian One Health National Report for Antimicrobial Use and Resistance - Mickaël Cargnel; Moira Kelly; Hein Imberechts; Boudewijn Catry; Maria-Eleni Filippitzi (MDPI AG, 2024)
(1) Background. Antimicrobial resistance (AMR) poses a substantial global health threat with profound economic implications. Acknowledging the imperative for a One Health (OH) strategy to combat this menace, Belgium introduced an annual national OH report, known as the "BELMAP report," encompassing antimicrobial use (AMU) and AMR, with the first edition completed in 2021. The integration of innovations for the healthcare system demands a meticulously planned process. (2) Methods. We introduced a three-step stakeholder analysis (SA) as a prospective framework for navigating this new report process, fostering complementary collaboration, pinpointing obstacles, suggesting approaches to overcome them, and facilitating national policy development. The SA unfolds in three steps: stakeholders identify and list their relevant activities, assess their positions regarding the BELMAP report, and complete "actor mapping" of national AMR and AMU stakeholders. (3) Results. Stakeholder identification reveals a fragmented landscape of AMR and AMU activities across Belgium. Assessment of stakeholder positions uncovers diverse expectations, collaborative challenges, and resource considerations. "Actor mapping" identifies key stakeholders, emphasizing the importance of high-interest and high-power actors. (4) Conclusions. This SA approach not only provides insights into the present stakeholder landscape in Belgium, it can also serve as a blueprint for other countries in the process of developing OH reports.